Promising Novelty in Articles: How Authors Publishing in Sinta and Scopus-Indexed Journals Differ or Resemble - Hasiyanti Hasiyanti; Safnil Arsyad; Zifirdaus Adnan (JEELS (Journal of English Education and Linguistics Studies), 2024)
Many academics have studied niche establishment tactics in journal articles, but none have studied two or more sets of journal articles in language studies. This study identifies how Scopus and Sinta English Language Teaching journal authors niche their research paper abstracts and introductions. Niche Establishment techniques in Sinta and Scopus-indexed journals were examined using qualitative and quantitative methods. This analysis used 100 Scopus- and Sinta-indexed research articles. From randomly selected journals' newest issues, research article parts were extracted. Most authors in the two sets of research publications define a niche in the introduction, but few do in the abstracts. Scopus-index journals use Strategy 2 (insufficient research) and Strategy 5 (suggesting solutions) the most, while Sinta-indexed journals use Strategy 2 and Strategy 1. For rookie authors and postgraduate students, this study proposes niche establishment tactics in research paper abstracts or introductions to improve writing.